Hydrography in the Navigable Part of the Zaire River - Bujika, Ngoy Mudia (The International Hydrographic Review, 2015)
This paper describes the navigable part of the Zaire River, the hydrographic surveys made in this lower part of the river and, finally, the tidal wave in the estuary. It should be pointed out that maintenance of the navigation channel as well as piloting of ships in the navigable part of the Zaire River are part of the duties of the ‘Régie des Voies Maritimes’, a technical and commercial public firm. This paper has been divided into four main chapters. The first one provides a general idea on the navigable part of the Zaire River. The second deals with hydrologie features (hydraulic, meteorological and sedimentological). The third encompasses all the hydrographic studies made in the navigable part of the Zaire River, particularly topographic, limnimetric, hydraulic, sedimentological and hydrometeorological as well as the hydrographic surveying. The fourth and last chapter describes the tide in the navigable part of the Zaire River.